Genetic analysis of preweaning growth in indigenous Gudali cattle under a long-term selection programme - Tawah, C.L.; Rege, J.E.O.; Mbah, D.A. (9th World Congress on Genetics Applied to Livestock Production, 1994)
Data for this study consisted of birth weight and 240-day weaning weight records of Ngaundere Gudali calves obtained from a selection experiment conducted at the Animal Production and Extension Farm on the Adamawa highlands of Cameroon and covered the period from 1971 through 1985. Direct heritabilities of birth weight (0.39+0.10) and weaning weight (0.27+0.09) were moderate. Maternal heritabilities of the two traits were 0.06+0.06 and 0.20+0.09, respectively. Direct-maternal genetic correlations were generally large and negative. Despite high calf losses, poor reproductive performance, and concomitant low selection intensities and long generation intervals, selection for 240-day weight yielded moderate genetic response (0.66 kg/yr).